The Potential of Acetylfuran and Furfural from Tamarindus indica as Lipoxygenase Inhibitor: In Silico Study - Apriani Herni Rophi; Yohanes Bare; Dewi Ratih Tirto Sari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2021)
Background: Tamarindus indica is a type of plant sub-family Caesalpinioideae, which is predicted to have anti-inflammatory properties. When inflammation occurs, arachidonic acid will undergo metabolism, the LOX pathway will release 5-lipoxygenase (5-LOX). Objective: This study aimed to analyze the potential of acetylfuran and furfural compounds on LOX action. Methods: The compound Acetylfuran (CID 14505), Furfural (CID 7362) were downloaded from the PubChem database. The 5-LOX protein was obtained from PDB (6N2W), preparation by removing ligands and molecules that bind to Discovery Studio V19.1.0.18287. Compound and protein interactions have interacted with the Vina autodock software integrated into the PyRX software and analyzed by Discovery Studio V19.1.0.18287. Results: The results showed that the content of Acetylfuran and Furfural compounds in Tamarindus indica is predicted to have the potential as an inhibitor of the LOX gene on different amino acid residues, namely 3 amino acid residues and 4 amino acid residues, respectively and produce binding energy. In addition, van der Waals forces, hydrogen and hydrophobic bonds were found, giving the strength of the bonds formed. Conclusion:  Bioactive acetylfuran and furfural have the potential as a drug to curve inflammation in the human body.